The Relevance of Nuclear Reactions for Standard Solar Models Construction - Villante, Francesco L.; Serenelli, Aldo (Frontiers in Astronomy and Space Sciences, 2021)
The fundamental processes by which nuclear energy is generated in the Sun have been known for many years. However, continuous progress in areas such as neutrino experiments, stellar spectroscopy and helioseismic data and techniques requires ever more accurate and precise determination of nuclear reaction cross sections, a fundamental physical input for solar models. In this work, we review the current status of (standard) solar models and present a detailed discussion on the relevance of nuclear reactions for detailed predictions of solar properties. In addition, we also provide an analytical model that helps understanding the relation between nuclear cross sections, neutrino fluxes and the possibility they offer for determining physical characteristics of the solar interior. The latter is of particular relevance in the context of the conundrum posed by the solar composition, the solar abundance problem, and in the light of the first ever direct detection of solar CN neutrinos recently obtained by the Borexino collaboration. Finally, we present a short list of wishes about the precision with which nuclear reaction rates should be determined to allow for further progress in our understanding of the Sun.